Protozoa and nematodes infecting Odontophrynus occidentalis (Anura, Odontophrynidae) from the Monte desert of Argentina - Piñeiro Gomez, Mauricio Daniel (2023)
The parasitofauna of amphibians from the province of San Juan has been studied very little. In particular, only one helminthological study has been reported on Odontophrynus occidentalis (Berg, 1896). The aim of the present study was to describe the endoparasites of O. occidentalis, including protozoa and nematodes. Twenty-one adults (13 males and 8 females) of O. occidentalis were analysed for parasites. Collected parasites were examined using standard parasitological techniques. Parasitological descriptors such as prevalence and mean intensity were calculated. Specimens belonging to the phyla Ciliophora and Nematoda were found in the intestinal tract. Protozoa of the genus Nyctotheroides and two nematode species, Aplectana hylambatis and Falcaustra sanjuanensis, were identified. This study provides new information on the new parasiticinfection of amphibians for the province of San Juan. We emphasize the need to increase the knowledge of the amphibian parasitofauna, mainly related to protozoa in these vertebrates, since the literature presents few reports.